Lama Pemakaian Masker KN95 Terhadap Jumlah Angka Kuman (STIKes Surya Global Yogyakarta, 2023)
Background: Coronaviruses (CoV) are large family of viruses that cause illnesses ranging from the common cold to more severe diseases such as Middle East Respiratory Syndrome (MERS-CoV) and Severe Acute Respiratory Syndrome (SARS-CoV). Problems that occur in Indonesia and around the world the use of masks are an obligation that must be done, one of which is using KN95 masks. Regarding the amount of use of KN95 masks, of course this can be found the possibility of the influence of the length of time wearing KN95 masks with the number of germs. The aims of this research is to examine the effect of the length of time wearing KN95 masks with the number of germs 6 hours and 8 hours during the current pandemic at STIKes Surya Global Yogyakarta.Methods: This research design used a parametric one way ANOVA test and normality and homogeneity test were carried out earlier before the Anacova test was conducted, with five samples and in every samples was repeated three times to know the number of germs on the mask, if the one way Anova test was not homogeneous, the test continues using the Kruskal Wallis non-parametric test followed by the Post hoc test.Results: There was a significant effect of the length of time wearing the KN95 mask on increasing the number of germs, it can be proven by using the Kruskall Wallis test which shows a result of 0.0200.05.Conclusion: There was a significant influence between the lengths of use of KN95 masks on the increase in the number of germs. The increase from 0 hours was 105 cells, 2 hours was 533.33 cells, 4 hours was 3,600 cells, 6 hours was 5,366.33 cells and 8 hours was 8750 cells per cm2 and of course this increase has a high risk of health problems if the KN95 mask is worn continuously.